1998
DOI: 10.1038/sj.leu.2401158
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing antibiotic resistance of Enterobacteriaceae by introducing a new antibiotic combination therapy for neutropenic fever patients

Abstract: Prompt empiric antibiotic therapy is of critical importance for patients with neutropenic fever. However, a major concern with important clinical consequences is the emergence of bacterial resistance to antibiotics. After using ceftazidime with a glycopeptide as initial empiric therapy for neutropenic fever, we were confronted with a 75% reduced susceptibility rate to ceftazidime of inducible Enterobacteriaceae collected in 1994. The initial empiric therapy was therefore replaced in May 1995 by a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…However, it is obvious that a thoughtful policy of antibiotic therapy should be in place in every transplant unit because a time relationship between antibiotic use and resistance has been well established and it is in departments which use antibiotics the most that the prevalence of resistant bacteria is the highest. 5,7,[12][13][14]16,17,19,24 There is no unique solution for the control of resistant strains but some steps can be considered 12,13,20,25,26 including constitution of an information and surveillance team, careful monitoring of the use of key antibiotics, staff education, and periodic rotation among systemic antibiotics with different modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is obvious that a thoughtful policy of antibiotic therapy should be in place in every transplant unit because a time relationship between antibiotic use and resistance has been well established and it is in departments which use antibiotics the most that the prevalence of resistant bacteria is the highest. 5,7,[12][13][14]16,17,19,24 There is no unique solution for the control of resistant strains but some steps can be considered 12,13,20,25,26 including constitution of an information and surveillance team, careful monitoring of the use of key antibiotics, staff education, and periodic rotation among systemic antibiotics with different modes of action.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study in our institute using disk diffusion found that all of the K. pneumoniae strains that were resistant to ceftazidime had an extendedspectrum β-lactamase enzyme (ESBL) [24]. Ceftazidime has been shown to play an important role in inducing gram-negative-producing ESBL [6,7,[25][26][27]. We suggest that effective therapy against ESBL producers should be considered in patients who fail to respond to ceftazidime and aminoglycoside.…”
Section: Discussionmentioning
confidence: 98%
“…The use of a ceftazidime-glycopeptide combination as initial empirical therapy for neutropenic fever resulted in a 75% reduced rate of susceptibility to ceftazidime among Enterobacteriaceae with AmpC b-lactamase-mediated resistance (Mebis et al, 1998).…”
Section: Use Of Ceftazidime With Cefepime In Hospitalsmentioning
confidence: 99%